A new species of free-living marine nematode (Nematoda: Chromadoridae) from the East China Sea - Chunming, Wang; Liguo, An; Yong, Huang (Zootaxa, 2015)
A new species of free-living marine nematodes, Ptycholaimellus longibulbus sp. nov., is described from the East China Sea. Ptycholaimellus longibulbus sp. nov. is characterized by having body length of about 1100–1400 μm, cephalic seta 9 µm long (half a head diameter), a relatively long double posterior pharyngeal bulb occupying 44–49% of pharyngeal length, a voluminous ventral gland with a large ampulla, cuticle with transverse rows of punctations and lateral differentiation with two longitudinal rows of thick dots, relatively long spicules 45–55 μm long, an arcuate gubernaculum 25 µm long, and a conico-cylindrical tail with a distinct long finger-like spinneret. A key to species of Ptycholaimellus is given.